PENCEGAHAN FRAUD: KOMPENSASI DAN KOMPETENSI SUMBER DAYA MANUSIA - Allysa, Mys. Friska; Periansya, Periansya; Sari, Yuliana (Jurnal Riset Terapan Akuntansi, 2024)
This research aims to determine the effect of Compensation and Competency on Fraud Prevention through Good Government Governance as an Intervening Variable. The population in this study were 117 employees of the South Sumatra Provincial Inspectorate with a sample selection technique of simple random sampling. This research is a quantitative study using primary data, namely a questionnaire with a research response of 54 employees at the South Sumatra Provincial Inspectorate. Data analysis used multiple linear regression analysis with the help of the SPSS version 2.9 program. The results of this research explain that Compensation has a negative and significant effect on Good Government Governance, Competence has no effect on Good Government Governance, simultaneously compensation and competence have an effect on Good Government Governance, Compensation has no effect on Fraud Prevention, Competence has no effect on Fraud Prevention, indirectly Compensation and Competence affect Fraud Prevention through Good Government Governance as an Intervening Variable. Keywords: Compensation, Competence, Good Government Governance, and Fraud Prevention.